1999
DOI: 10.1021/jf981054j
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Activity of Glycitein, a Soy Isoflavone

Abstract: Glycitein (4' ,7-dihydroxy-6-methoxyisoflavone) accounts for 5−10% of the total isoflavones in soy food products. The biological activity of this compound has not been reported to date, although numerous studies have been performed with the other soy isoflavones, daidzein and genistein. Glycitein was isolated from soy germ to 99% purity. Weaning female B6D2F1 mice were dosed with glycitein (3 mg/day), genistein (3 mg/ day), and diethylstilbestrol (DES) (0.03 μg/day) in 5% Tween 80 by gavage for 4 days. A contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(78 citation statements)
references
References 16 publications
4
70
1
3
Order By: Relevance
“…10) Interestingly, the synthetic isoflavone, ipriflavone (7-isopropoxy-3-phenyl-4H-1-benzopyran-4-one), which is structurally similar to soy isoflavones, is devoid of estrogenic activity, but is effective in preventing the unfavorable changes in serum cholesterol associated with ovarian hormone deficiency in the ovx animals. 23) We found in this study that daidzin and glycitin treatment effectively prevented the ovxinduced rise in serum lipids, total cholesterol and triglycerides, as estrone did.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…10) Interestingly, the synthetic isoflavone, ipriflavone (7-isopropoxy-3-phenyl-4H-1-benzopyran-4-one), which is structurally similar to soy isoflavones, is devoid of estrogenic activity, but is effective in preventing the unfavorable changes in serum cholesterol associated with ovarian hormone deficiency in the ovx animals. 23) We found in this study that daidzin and glycitin treatment effectively prevented the ovxinduced rise in serum lipids, total cholesterol and triglycerides, as estrone did.…”
Section: )mentioning
confidence: 99%
“…7,8) Both in vitro and in vivo studies have shown that daidzein, genistein, and their glycosides exert a weak estrogenic effect. 9) Therefore, numerous studies have been performed with daidzein and genistein, but there has been only one biological study on the estrogenic activity of glycitein in vitro and in vivo, 10) to our knowledge. Several investigators have reported that soybean consumption may contribute to lower risk of the postmenopausal diseases, including coronary heart disease 11) and osteoporosis.…”
mentioning
confidence: 99%
“…Most phytoestrogenic flavonoids have hydroxyl groups located at the 7-and 4 0 -positions, such as genistein, daidzein and glycitein. 1,3,4 On-line identification of phytochemical constituents in plant extracts is a major issue in phytochemistry, since a timeconsuming isolation procedure for confirmatory purposes can be avoided. Liquid chromatography (LC) combined with diode array detection (DAD) and mass spectrometry (MS) is a powerful tool for identification and/or partial structure elucidation of unknowns.…”
mentioning
confidence: 99%
“…When the uterine weights were analysed after euthanisation on the fifth day, only daidzin significantly increased the uterine weight of the mice after the values had been corrected for initial body weight (Farmakalidis & Murphy, 1984). Song et al (1999) performed similar studies with glycitein, demonstrating that the compound had stronger oestrogenic activity in the uterotrophic assay than genistein. In studies on the competitive binding abilities with 17β- [H 3 ] estradiol to the oestrogen receptor proteins of mouse uterine cytosol, diethylstilbestrol had 95% of the activity of 17β-estradiol, genistein 0.49%, daidzein, 0.027%, and glycitein 0.028%.…”
Section: Relevant Phytoestrogens In a Food And Feed Contextmentioning
confidence: 77%